Ritus Lodong Ana’ dalam Masyarakat Lamaholot dan Sakramen Baptis: Pengantar Sebuah Perbandingan - Lio, Zakeus Daeng (Perspektif, 2014)
For the ethnic society of Lamaholot, East Flores, a baby is a gift of Lera Wulan Tana Ekan (God), therefore the people have to perform a special ritual called Lodong Ana’. The ritual is performed with double intentions, namely for thanking the almighty God spiritually and for incorporating the baby into the society socio-culturally. As any common ethnic ritual of agricultural society around the globe, the Lodong Ana’ rite is performed with its various symbols representing the society and prayers uttered by the kepala adat (ethnic chief). This ritual has some similarities with the Sacrament of Baptism in the Catholic Church. This article, then, tries to describe parallelism between the two. The writer argues that the dialogue between the two rites is of paramount importance, particularly for the people of Lamaholot who are Catholics. The constructive and critical dialogue is mostly possible, which can contribute for strengthening the bond of family life in the society at large as well as Christian community as people of God with its local flavour.